2011
DOI: 10.1029/2010ja015871
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the response of the ionosphere-magnetosphere system to sudden solar wind density increases

Abstract: 1] The different responses of the magnetosphere to sudden solar wind density enhancements are investigated. The majority of the responses are observed to have two phases: the first is due to an inductive E field propagating through the system, while the second is due to a vortex formation in the magnetosphere. However, during some events, the system displays a single-phase response. In order to understand the controlling parameters in the system response, statistical analyses of several solar wind external cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 38 publications
(64 reference statements)
7
48
0
Order By: Relevance
“…Although the IMF B y generally contributes to the dawn-dusk asymmetry and may be the reason for the asymmetric MI of event 1, it is not likely the cause of the asymmetric PI responses because the IMF |B y | is large in events 1-3 but the PI asymmetry is seen in events 2 and 4. The Alfvén Mach number is known to alter the SC responses (Yu and Ridley 2011), but the numbers in events 1-3 are in the same range (7-8) and thus do not explain the PI asymmetry. Liu et al (2011) inferred that fading of a discrete aurora in the post-noon sector corresponds to the PI phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the IMF B y generally contributes to the dawn-dusk asymmetry and may be the reason for the asymmetric MI of event 1, it is not likely the cause of the asymmetric PI responses because the IMF |B y | is large in events 1-3 but the PI asymmetry is seen in events 2 and 4. The Alfvén Mach number is known to alter the SC responses (Yu and Ridley 2011), but the numbers in events 1-3 are in the same range (7-8) and thus do not explain the PI asymmetry. Liu et al (2011) inferred that fading of a discrete aurora in the post-noon sector corresponds to the PI phase.…”
Section: Resultsmentioning
confidence: 99%
“…The locations and propagation of the FACs provide useful information about the magnetospheric drivers, where the PI and MI currents are related to inertial currents of the compressional wave propagating through the magnetosphere and diamagnetic currents of tailward-propagating pressure structures behind the compressional wave, respectively. In addition, the interplanetary magnetic field (IMF) B y , B z , and Alfvén Mach number are known to alter FAC locations (Yu and Ridley 2011;Peng et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The state of the magnetosphere is controlled by solar wind conditions at the upstream outer boundary (32 R e ) and ionosphere conditions at the inner boundary (spherically 2.5 R e ). The solar wind conditions at the upstream boundary can be obtained either from other model output [e.g., Ridley , ] or from real observations such as Advanced Composition Explorer (ACE) or Wind measurements [e.g., Yu and Ridley , ] or even from user‐designed conditions [e.g., Yu and Ridley , ]. Other outer boundaries use zero gradient in the solar wind plasma parameters because these boundaries are too far from the Earth to influence the near‐Earth dynamics.…”
Section: Methodsmentioning
confidence: 99%
“…The magnitudes of the slopes (<1) indicate damped amplitudes of AMDs, although they are proportional to the MI amplitude. Recently, a new feature of the ionospheric flow variations after the main impulse of SI was noticed in the SuperDARN observations (Hori et al 2012) and also in simulations (Yu and Ridley 2011;Fujita et al 2012). Hori et al (2012) found multiple oscillations after the MI of a negative impulse in a northward IMF condition.…”
Section: Magnetic Field Variations After Maximum Deviationmentioning
confidence: 99%
“…Very recently, a few studies have investigated the ionospheric flow patterns after the occurrence of an MI. The multiple undulating structures in ionospheric flow variations and in ground magnetic variations have been noted through observational and simulation studies (Yu and Ridley 2011;Hori et al 2012;Fujita et al 2012). Several mechanisms (such as the flow vortex chain in the magnetopause region due to the rebound of the magnetopause, multiple ionospheric convection, and compressional wave bouncing between the ionosphere and the dayside magnetopause) have been sought to explain these oscillations.…”
mentioning
confidence: 99%